The exploitation of mountain natural resources during the Iron Age in the Eastern Pyrenees: the case study of production unit G at Tossal de Baltarga (Bellver de Cerdanya, Lleida, Spain) - Olesti, Oriol; Morera, Jordi; Oller, Joan; Carrasco, Jose M.; Colominas, Lídia; Portillo, Marta; Berrocal, Anna; Lopez-Bultó, Oriol; Obea, Laura; Tarifa, Nadia; Tárraga, Paula; Sisa-López de Pablo, Joaquim; et al. (Frontiers in Environmental Archaeology, 2024)
The Iron Age site of Tossal de Baltarga (Bellver de Cerdanya) was a large Iberian residential complex occupying a strategic position in the middle of the Eastern Pyrenees. It was completely destroyed by fire in the second half of the 3rd c. BC., preserving in certain areas an important volume of archaeological and bioarchaeological material. This is the case of Building G, a twostorey construction whose violent blaze has offered the possibility of analysing a precise moment in the history of an Iron Age productive unit. The existence of a stable on the lower floor, where four sheep, a goat and a horse were documented, and an upper floor where textile production and storage were evidenced, allows us to analyse the complexity of the economic activities and exploitation of local resources, such as livestock, agriculture, forestry and mining.